Communicating Dissatisfaction over International Norms: Unpacking Chinese International Discursive Strategy to Oppose the US in the South China Sea - Grandpierron, Matthieu; Pomès, Eric (Sociološki pregled, 2025)
This paper investigates these questions from the perspective of official Chinese discourses related to the South China Sea dispute. Beginning with the key assumption that what matters more to understanding how the Chinese view the international order is not what they say but how they say it, this article uses a mixed-method approach to critical discourse analysis in order to unpack the implicit meanings of official Chinese narratives. The quantitative analysis of these speeches reveals that emotions (humiliation, anger, and feelings of superiority) are important, along with the political use of history to create narratives aiming to legitimize China’s desire to remove the United States from the management of Asia-Pacific issues. The paper will also show that while the Chinese discourse remains the same under all US administrations, the Chinese legal discourse has fluctuated as the dispute has evolved. Such findings provide a better understanding of Chinese political communication on international law and on the present international order.